THE REPRESENTATION OF RACISM IN ALAN PATON'S CRY, THE BELOVED COUNTRY(An Analysis of Racism Representation in Alan Paton's Novel Cry,the Beloved Country) - Astri Novianti, - (2011)
This research paper is entitled The Representation of Racism in Alan Paton's Cry, the Beloved Country. The purpose of this study is to investigate how racism is represented in the novel through the experiences of the characters and the character's reaction toward racism as evidenced in the novel. The study employs descriptive analysis. The study uses a descriptive-qualitative design and applies close reading strategy to read the text. The data were in the form of words, phrases, and sentences obtained through reading the text. Shirley Better, Tracy E Ore, and Phillip T. Gay's theory of racism have been used to analyze the data. The research finds that racism in the novel is represented in individual racism, institutional racism, and societal or cultural racism. This is manifested in the way the white people show their dominance and power against the black people. The research also found different reaction toward racism shown by the characters. Some of the characters just accept the racism, some accept racism with minor resistance, and some other reject racism and make plans to take revenge. The research concludes that first; racism builds social status differences among people. Because of racism, people with different race are considered to have different social status, some of them are considered inferior and have a lower social status than other. Second, Racism separates people even in a place in which they worship the same God, and third, Racism robs the opportunity of some people for a better life trough education. This paper is expected to provide a valuable contribution for the students who are interested in conducting research focusing on modern literary criticism, especially for those who are interested investigating novels. It is also expected that this paper may enrich student's knowledge and their understanding of literary theories.